How pyruvate postpones postharvest physiological deterioration of cassava - Yannian Che; Chen Shen; Xiaohua Lu; Zhongping Ding; Yaxingqiao Zhou; Qin Zhou; Jiao Liu; Yajie Wang; Jianchun Guo; Yuan Yao; Alisdair R. Fernie; Ruimei Li (Postharvest Biology and Technology, 2026)

Mechanism of glyoxalase MeGLYI-13 in regulating postharvest physiological deterioration of cassava - Chen Shen; Yannian Che; Zhongping Ding; Qin Zhou; Yaxingqiao Zhou; Alisdair R. Fernie; Jiao Liu; Yajie Wang; Xiaohua Lu; Jianchun Guo; Yuan Yao; Ruimei Li (Postharvest Biology and Technology, 2026)

Quantifying the effects of near-fault fling-step ground motions on seismic performance of offshore wind turbines - Wei Che; Guowei Qin; Yajun Li; Chao Long (Ocean Engineering, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Oxygen vacancy enriched alumina supported Ni nanocatalysts for highly selective acetylene hydrogenation - Hedan Yao; Yuanjun Che; Dong Huang; Yi Qin; Yuchen Niu; Wenhong Li; Liuyi Pan; Dong Li (Chemical Engineering Journal, 2026)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Estimating AVHRR snow cover fraction by coupling physical constraints into a deep learning framework - Qin Zhao; Xiaohua Hao; Tao Che; Donghang Shao; Wenzheng Ji; Siqiong Luo; Guanghui Huang; Tianwen Feng; Leilei Dong; Xingliang Sun; Hongyi Li; Jian Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

Novel insights into the mechanism of dynamic changes in microstructure and physicochemical properties of corn straw pretreated by ball milling and feasibility analysis of anaerobic digestion - Youpei Qu; Xinying Miao; Shaopeng Chen; Nan Qin; Jiangnan Li; Yuchen Che; Lina Luo; Yong Sun (Science of The Total Environment, 2024)

Effects of sulfate on survival, osmoregulation and immune inflammation of mud crab(Scylla paramamosain) under low salt conditions - Yun Hu; Gao Gao; Kangxiang Qin; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Aquaculture, 2024)

Improve flotation efficiency of refractory tungsten ore and reduce carbon emission in flotation process: A case study of Sandaozhuang deposit in Henan, China - Wei Li; Fen Jiao; Xu Wang; Wenfang Che; Zhengquan Zhang; Baijun Xin; Min Xu; Wenqing Qin (Minerals Engineering, 2024)

Circ_0090231 knockdown protects vascular smooth muscle cells from ox-LDL-induced proliferation, migration and invasion via miR-942-5p/PPM1B axis during atherosclerosis - Jian Yang; Xiangyan Li; Yuming Zhang; Pengfei Che; Wei Qin; Xuecui Wu; Yue Liu; Bing Hu (Molecular and Cellular Biochemistry, 2024)

Correlation of gut microorganisms and non-volatile flavor substances provides new insights for breeding Scylla paramamosain - Gao Gao; Xing Li; Kangxiang Qin; Yun Hu; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Journal of Oceanology and Limnology, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Vegetable residues retention: An effective and environment friendly way to handle tomato wastes from greenhouse production - Xiaomei Sun; Sijin Chen; Huan Li; Jinxia Li; Guojun Han; Haobing Dong; Jiangwei Che; Qin Zhang (European Journal of Soil Biology, 2024)

ICEEMDAN/LOESS: An Improved Vibration-Signal Analysis Method for Marine Atomic Interferometric Gravimetry - Jinxiu Ma; An Li; Fangjun Qin; Wenbin Gong; Hao Che (Journal of Marine Science and Engineering, 2024)
The marine atomic interferometric gravimeter is a vital precision instrument for measuring marine geophysical information, which is widely used in mineral resources exploration, military applications, and missile launches. In practical measurements, vibration disturbance is an important factor that affects measurement accuracy. This paper proposes the combination of improved complete ensemble empirical mode decomposition with adaptive noise and locally weighted regression for vibration characterization of gravimeter vibration data. Firstly, the original signal is added into a pair of white noise for adaptive noise-complete ensemble empirical mode decomposition to obtain multiple intrinsic mode functions. The efficient IMF components and noise components are filtered out under the dual indicators of correlation coefficient and variance contribution ratio, and then the LOESS filtering method is used for noise reduction to obtain useful signal detail information; finally, the noise-containing components are reconstructed with the effective components after the noise-reduction process. The experimental results of both simulated and measured vibration signals show that the proposed method can effectively decompose the different high- and low-frequency bands contained in the vibration signal and remove the noise of the original signal.

Mutagenicity of PM2.5 and Ethnic Susceptibility in Chengdu-Chongqing Economic Circle, China - Shumin Zhang; Qin Zhang; Xiaomeng Li; Ronghua Zhang; Hanxiong Che; Zhenzhong Liu; Dongmei Guo; Fumo Yang; Yang Chen (Science of The Total Environment, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Increased litter input significantly changed the total and active microbial communities in degraded grassland soils - Rongxiao Che; Dong Liu; Jinling Qin; Fang Wang; Weijin Wang; Zhihong Xu; Linfeng Li; Jinming Hu; Iman Tahmasbian; Xiaoyong Cui (Journal of Soils and Sediments, 2020)

Effects of network topologies on stochastic resonance in feedforward neural network - Jia Zhao; Yingmei Qin; Yanqiu Che; Huangyanqiu Ran; Jingwen Li (Cognitive Neurodynamics, 2020)

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)